Pop goes the Pope: religion and popular music in Italy - Paolo Prato (Taylor & Francis Group, 2021)
Music has maintained a long relationship with cult since ancient times, contributing to its efficacy and strengthening a communitarian identity. The advent of Christianity marked a sensible change in the way music was used, pioneering the very idea of listening as absolute, later extended to Western art music. The spread of popular music in the twentieth century impacted on religion too and the Christian world was particularly affected from the Second Vatican Council on, both within liturgy and in secular activities. A strong impulse to legitimate and even welcome sounds and practices from pop and rock culture was given by John Paul II, in 1997 during a concert featuring the future Nobel Prize Winner Bob Dylan. The article explores this changing relationship from an interdisciplinary perspective, borrowing from history, musicology, anthropology, sociology, theology, and cultural studies, as suggested by the ‘media, religion and culture’ approach. The first part reviews the historical steps leading to contemporary soundscape with respect to religion. The second part focuses on three case-studies, each representing a distinct point of view: that of traditional music revived, centered on collectivity; that of auteur music, centered on the power of the word; that of crossover pop, aimed at offering an aesthetic experience.